Institutional Causes of the Global Banking Crisis and the Emergence of Macro-Prudential Countercyclical Policy - Sławiński, Andrzej (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The recent global banking crisis was caused by an intertwined process consisting of the emergence of universal financial conglomerates, the development of global interbank money markets, and of regulatory capture leading to an excessively libertarian approach to financial regulation and supervision. All these factors produced the three main sources of risks that brought about the global banking crisis, namely, enhanced credit pro-cyclicality, banks' interconnectedness, and their growing exposure to balance sheet losses. The experiences with unsustainable lending booms of the previous decade showed that stabilizing inflation is not sufficient to stabilize the economy. These experiences underscore that macro-prudential policy should be a second weapon in central banks' countercyclical policy arsenal.